Evaluating the impact of remittances on human capital investment in the Kyrgyz Republic - Xin Gao; Aiko Kikkawa; Jong Woo Kang (Asian Development Bank (ADB), 2021)
Remittances from overseas can encourage human capital investment and improve educational outcomes in developing countries. Empirical studies, however, have shown mixed evidence at best. This paper uses a 5-year panel dataset that tracks the same 3,000 households and 8,000 individuals through time in all seven regions of the Kyrgyz Republic to examine the impact of remittances on the human capital formation of school-age children. After correcting for selection bias and other potential endogeneities with instrumental variables and fixed effects regressions, remittances are found to have negative impacts on human capital investment and educational achievement. The negative effects can be attributed in part to recipients' increased expenditure on durable goods and extended hours of child labor on farm work as a compensation for missing adult labor. Our finding calls for actions that mitigate the negative effects and incentivize families to spend remittances on education, including financial literacy education, better monitoring of farm labor hours of school-age children, and targeted investment to improve the quality of education services in the Kyrgyz Republic.
Keywords: D13; F22; F24; O15; 330; education; household expenditure; human capital investment; Kyrgyz Republic; labor migration; remittances